2022
DOI: 10.1021/acs.joc.2c00207
|View full text |Cite
|
Sign up to set email alerts
|

Remote Stereoelectronic Effects in Pyrrolidone- and Caprolactam-Substituted Phenols: Discrepancies in Antioxidant Properties Evaluated by Electrochemical Oxidation and H-Atom Transfer Reactivity

Abstract: New antioxidants are commonly evaluated via two main approaches, i.e., the ability to donate an electron and the ability to intercept free radicals. We compared these approaches by evaluating the properties of 11 compounds containing both antioxidant moieties (mono- and polyphenols) and auxiliary pharmacophores (pyrrolidone and caprolactam). Several common antioxidants, such as butylated hydroxytoluene (BHT), 2,3,5-trimethylphenol (TMP), quercetin, and dihydroquercetin, were added for comparison. The antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Thus, it has recently been shown that, within certain classes of antioxidants, their oxidative potentials correlate with the rate constants of their interaction with the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH). 31 Figure 5 shows that, in general, there is a semiquantitative correlation of "the lower the oxidation potential, the higher the rate of oxidative addition", despite some exceptions that strongly distort it. The cases of thiophene and triethylamine are the most striking, showing kinetics relatively lower than what would be expected from the oxidation potentials of their complexes with 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has recently been shown that, within certain classes of antioxidants, their oxidative potentials correlate with the rate constants of their interaction with the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH). 31 Figure 5 shows that, in general, there is a semiquantitative correlation of "the lower the oxidation potential, the higher the rate of oxidative addition", despite some exceptions that strongly distort it. The cases of thiophene and triethylamine are the most striking, showing kinetics relatively lower than what would be expected from the oxidation potentials of their complexes with 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, the reactivity can be predicted on the basis of the oxidation potential, which is determined quickly and easily. Thus, it has recently been shown that, within certain classes of antioxidants, their oxidative potentials correlate with the rate constants of their interaction with the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) …”
Section: Resultsmentioning
confidence: 99%
“…Generally, there is a correlation between antioxidant and pro-oxidant activity and oxidation potential. However, the connection between the ability to donate an electron and the ability to intercept radicals is not always straightforward and exceptions do exist [ 42 ], especially when multiple redox-active groups are present.…”
Section: Resultsmentioning
confidence: 99%